Cardiac Aspect of Coronavirus Disease 2019 (COVID-19) in Children - Isa Tafreshi, Roya (Journal of Pediatric Nephrology, 2020)
Coronavirus disease 2019 (COVID-19) is a global pandemic with more than a million confirmed cases of COVID-19 and more than 130,000 deaths reported worldwide. The major morbidity and mortality from COVID-19 are large because of acute viral pneumonitis that evolves to acute respiratory distress syndrome. Cardiac injury is one of the common complications of COVID-19. Furthermore, preexisting cardiovascular disease is one of the important risk factors for mortality among the patients. Evidence of cardiac involvement is common among patients hospitalized with COVID-19, but the causes of myocardial injury have not been completely explained. COVID-19 appears to be milder in children than in adults and fewer children seem to have developed severe respiratory distress. The aim of this article is a brief review of cardiovascular involvement in COVID-19 with a focus on cardiac disease in children. Keywords: COVID-19; Corona virus disease 2019; Cardiac complication; Cardiovascular disease; Arrhythmia; Mortality; Child.